Accuracy of Bioelectric Impedance Analysis Devices to Estimate Body Fat and Fat-Free Mass in College Women Athletes - Ashly Hilfer; Allison Oligchlaeger; Madison Henderson; Molly Whitehead; Jana Arabas; Jerry Mayhew; Jeremy Houser (International Universities Strength and Conditioning Association, 2023)
Background: Body composition is frequently measured in women athletes to evaluate training changes, assist in dietary planning, and avoid the female athlete triad. Measurements to monitor %fat and fat-free mass (FFM) can provide valuable information for coaches and athletes throughout the training process. However, questions remain concerning the accuracy of various methods used to measure %fat. The purpose of this study was to assess the accuracy of bioelectric impedance analysis (BIA) devices to estimate %fat and FFM compared to dual-energy X-ray absorptiometry (DXA) in college women athletes. Methods: A cross-section design was employed to assess %fat and FFM among college women athletes. Fiftyseven athletes (age = 20.0   1.4 yrs, height = 179.2   6.0 cm, weight = 74.3   4.4 kg) from soccer (n = 29), basketball (n = 15), and swimming (n = 13) had %fat estimated from four single-frequency BIA devices. Two BIA devices had general population equations (BIA1 and BIA2) and two had athletespecific equations (BIA3 and BIA4). Each device had proprietary equations for estimating %fat and was not capable of being updated. Each device had a 2-point electrode contact with either hands or feet. DXA %fat served as the criterion measurement. Percent fat was estimated directly by each device, and FFM was calculated as body mass minus fat mass. All measures were completed in single sessions for each athletic group with different sports groups being measured at the onset of their competitive season. Athletes were measured between 1400 and 1600 hours in a rested stated with hydration assumed and after voiding the bladder. A repeated-measures one-way analysis of variance (ANOVA) with Bonferroni post hoc testing was used to evaluate differences among measurement techniques with significance set at p<0.05. Results: Three arm-to-arm BIA devices (BIA1, BIA2, and BIA3) were not significantly different in %fat estimates (23.1 ± 5.0%, 23.7 ± 4.7%, and 23.6 ± 4.3%, respectively) but were significantly lower than DXA (29.5 ± 5.1%). The leg-to-leg athletic BIA (BIA4) had a significantly higher %fat estimate (24.6 ± 5.7%) than BIA1 but was not significantly different from BIA2 and BIA3. The correlation of DXA %fat with BIA1 (r = 0.84), BIA2 (r = 0.85), and BIA3 (r = 0.85) were significant but not statistically different across the 3 devices. BIA4 had a significantly lower correlation (r = 0.66) with DXA %fat. The lower estimates in %fat resulted in significantly higher calculated FFM values for BIA1 (51.1 ± 5.5 kg), BIA2 (50.8 ± 59 kg), BIA3 (50.9 ± 6.9 kg), and BIA4 (50.1 ± 5.8 kg) than for DXA (47.5 ± 5.9 kg). However, all BIA estimates of FFM were highly correlated with DXA FFM (r = 0.90-0.93). Limits of agreement analysis indicatedthe average bias ranged from 2.2 kg (BIA4) to 3.4 kg (BIA1). Conclusion: Single-frequency BIA devices utilized in this study tend to underestimate %fat and overestimate FFM compared to DXA in college women athletes. However, high correlations between predicted and actual FFM values indicate that single-frequency BIA devices may be useful for tracking changes in women athletes across seasons.